Disorientation, self-awareness and ongoing learning: student midwives’ experiences of clinical placements in Italy - Borrelli, Sara E.; Cattaneo, A.; Recalcati, R.; Nespoli, Antonella (MIDIRS, 2017)
Objective: To explore student midwives’ perspectives, experiences and concerns regarding clinical placements in the Italian setting. Design: A qualitative phenomenological study was undertaken, with data collected through semi-structured interviews and diaries. Ethical approval was obtained. Data analysis was conducted using a thematic analysis approach. Setting: One university in Northern Italy including a midwifery undergraduate programme. Participants: Purposeful sample of 19 third-year student midwives. Findings: Four themes emerged from the data: a) becoming a midwife: disorientation, self-awareness and ongoing learning; b) mentor as key figure; c) practice and theory: a ‘chicken and egg’ situation; d) clinical placements: a window on the uniqueness of the midwifery profession. Student midwives reported a journey through different learning phases within clinical placements, from feeling disoriented while facing initial challenges in the first year of the course to having increasing awareness of their role in the second and third year of the programme. The phase of disorientation was mainly due to not being aware of the theoretical evidence behind practice, not feeling part of the team, not knowing what their role was and lack of appropriate supervision from mentors. A positive relationship with the mentor encouraged students to share perspectives and doubts, stimulating a problem solving approach. The students found it helpful when the mentor involved them in the decision making and praised them when they deserved it. A good rapport with the midwife was reported by the participants as inspiring self-confidence and cognitive enquiries; it also allowed the students to feel part of the multidisciplinary team. An overall sense of ongoing learning was still present at the end of the midwifery programme. Key conclusions and implications for practice: Continuity of mentorship and mentors’ commitment to supporting students emerged as key aspects for a positive and fruitful learning experience within practice settings. Other pivotal elements to be considered by mentors are making the students feel welcome and part of the team; orienting them on the first day of placement; allowing some time for familiarisation with the placement area and clinical policies; involving the students in the decision-making process and care planning/implementation/ evaluation. Appropriate national mandatory training should be put in place for mentors to allow a more effective learning experience in practice settings for student midwives.